Gunn and Heid: Teaching small group development with reality TV. Issue 2 (3rd April 2017) - Kopaczewski, Shana
Abstract : Courses: Small group communication or any courses with units on group/team work. Objective: In this single-class activity, students will use reality TV to identify Tuckman's five phases of group development: forming, storming, norming, performing, and adjourning. Students analyze how phases of group development manifest through group interaction and ultimately contribute to group performance.